2017
DOI: 10.3389/fmicb.2017.00827
|View full text |Cite
|
Sign up to set email alerts
|

Technological Microbiology: Development and Applications

Abstract: Over thousands of years, modernization could be predicted for the use of microorganisms in the production of foods and beverages. However, the current accelerated pace of new food production is due to the rapid incorporation of biotechnological techniques that allow the rapid identification of new molecules and microorganisms or even the genetic improvement of known species. At no other time in history have microorganisms been so present in areas such as agriculture and medicine, except as recognized villains.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 279 publications
(281 reference statements)
0
27
0
1
Order By: Relevance
“…This unique phenomenon have revealed the biological basis of the strong metabolic function of BC and provided perspectives for future studies on investigating interactions between the gut microbiomes and the external environment based on network and invasion hypotheses. Many studies have confirmed that some insect gut bacteria possess the ability to degrade refractory substances (Li et al ., 2017a; Yang et al ., ), and many bacteria can also enhance or alter their metabolic functions through genetic engineering (Vitorino and Bessa, ; Panda et al ., ). Considering that approximately half of the raw FW dry matter remained after 10 days of BC in our study, the colonization attempts by other insect‐oriented or commercialized bacterial strains were worth further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This unique phenomenon have revealed the biological basis of the strong metabolic function of BC and provided perspectives for future studies on investigating interactions between the gut microbiomes and the external environment based on network and invasion hypotheses. Many studies have confirmed that some insect gut bacteria possess the ability to degrade refractory substances (Li et al ., 2017a; Yang et al ., ), and many bacteria can also enhance or alter their metabolic functions through genetic engineering (Vitorino and Bessa, ; Panda et al ., ). Considering that approximately half of the raw FW dry matter remained after 10 days of BC in our study, the colonization attempts by other insect‐oriented or commercialized bacterial strains were worth further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This contemporary and applied microbiology is known as Technological Microbiology and has employed complex techniques, such as heterologous expression and metabolic engineering, to generate new products and improve products and services [202].…”
Section: Why Should We Know About Microbial Diversity?mentioning
confidence: 99%
“…For example, microbial bioplastics are currently used to manufacture medical materials, including films used as drug-delivery vehicles [241] or materials used in civil construction, making construction less expensive and more efficient [242]. The prospect of discovering new microorganisms or new properties in already known microorganisms, and the possibility of modifying them through genetic engineering, or even the possibility of stimulating naturally expressed pathways to elicit the synthesis of metabolites of interest, illustrates the importance of microbial biodiversity in strengthening Technological Microbiology [202], which has greatly affected the daily lives of people by providing new products and services.…”
Section: Why Should We Know About Microbial Diversity?mentioning
confidence: 99%
“…The microbial biodiversity in Brazil and the possibility of using agricultural and industrial residues as substrates, justify the search for new microorganisms producing enzymes with desirable characteristics that can be applied industrially (Vitorino andBessa 2017, Costa 2014).…”
Section: Introductionmentioning
confidence: 99%